Emergence of representative signals for sudden stratospheric warmings beyond current predictable lead times - Z. Wu; B. Jiménez-Esteve; R. de Fondeville; E. Székely; G. Obozinski; W. T. Ball; D. I. V. Domeisen (Weather and Climate Dynamics, 2021)
Major sudden stratospheric warmings (SSWs) are extreme wintertime circulation events of the Arctic stratosphere that are accompanied by a breakdown of the polar vortex and are considered an important source of predictability of tropospheric weather on subseasonal to seasonal timescales over the Northern Hemisphere midlatitudes and high latitudes. However, SSWs themselves are difficult to predict, with a predictability limit of around 1 to 2 weeks. The predictability limit for determining the type of event, i.e., wave-1 or wave-2 events, is even shorter. Here we analyze the dynamics of the vortex breakdown and look for early signs of the vortex deceleration process at lead times beyond the current predictability limit of SSWs. To this end, we employ a mode decomposition analysis to study the potential vorticity (PV) equation on the 850 K isentropic surface by decomposing each term in the PV equation using the empirical orthogonal functions of the PV. The first principal component (PC) is an indicator of the strength of the polar vortex and starts to increase from around 25 d before the onset of SSWs, indicating a deceleration of the polar vortex. A budget analysis based on the mode decomposition is then used to characterize the contribution of the linear and nonlinear PV advection terms to the rate of change (tendency) of the first PC. The linear PV advection term is the main contributor to the PC tendency at 25 to 15 d before the onset of SSW events for both wave-1 and wave-2 events. The nonlinear PV advection term becomes important between 15 and 1 d before the onset of wave-2 events, while the linear PV advection term continues to be the main contributor for wave-1 events. By linking the PV advection to the PV flux, we find that the linear PV flux is important for both types of SSWs from 25 to 15 d prior to the events but with different wave-2 spatial patterns, while the nonlinear PV flux displays a wave-3 wave pattern, which finally leads to a split of the polar vortex. Early signs of SSW events arise before ...